2022
DOI: 10.1111/anec.12986
|View full text |Cite
|
Sign up to set email alerts
|

Tricuspid regurgitation in His bundle pacing: A systematic review

Abstract: Objective This systematic review aimed to explore an association of new TR and its quantification in patients undergoing His bundle pacing (HBP). Methods A literature review was conducted using Mesh terms (His bundle pacing, tricuspid regurgitation, tricuspid valve incompetence, etc.) in PubMed, EMBASE, Web of science CINAHL, and the Cochrane Library till October 2021. Relevant studies evaluating tricuspid regurgitation in HBP were included and information regarding TR and its related factors (ejection fractio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 54 publications
(58 reference statements)
3
15
0
Order By: Relevance
“…A 2022 systematic review by Zaidi et al . 3 found results that were comparable with those of Stassen et al for the use of His bundle pacing. Of the 10 studies considered in the review four studies showed an improvement in TR grade following HBP at 12–17 month follow-up.…”
supporting
confidence: 84%
See 1 more Smart Citation
“…A 2022 systematic review by Zaidi et al . 3 found results that were comparable with those of Stassen et al for the use of His bundle pacing. Of the 10 studies considered in the review four studies showed an improvement in TR grade following HBP at 12–17 month follow-up.…”
supporting
confidence: 84%
“…Of the 10 studies considered in the review four studies showed an improvement in TR grade following HBP at 12–17 month follow-up. 3 Wu et al conducted a study comparing His bundle pacing in candidates for CRT and concurred with the results of Zaidi et al ., as they found baseline TR had reduced at 12 month follow-up. 4 …”
supporting
confidence: 57%
“…However, in a meta-analysis of eight observational studies and two randomized clinical trials involving 546 patients who underwent His-bundle pacing, there were mixed outcomes with some studies reporting overall decrease in TR and other studies demonstrating increased TR from baseline. 50 Similarly, the concept was not supported in a comparison of 472 patients who received either left bundle branch area pacing or RV septal pacing with the same thin Medtronic 3830 lead (SelectSecure System, Medtronic, Inc.); the rate of worsening TR at 1 year (15.2% vs. 17.2%; p > .05) and 2 years (21.6% vs. 24.6%; p > .05) was similar between groups. 51 A shorter distance between the electrode fixation site to the tricuspid annulus was found to discriminate the risk of worsening TR, such that TR progression was highest in patients with leads <1.9 cm from the annulus.…”
Section: Physiologic Pacing Strategiesmentioning
confidence: 99%
“…Stimulation of the His bundle seems to be the most physiological technique and the least related to secondary TR evoked by pacing. 62 In some cases, epicardial leads are used. 53 Other solutions may involve a subcutaneous ICD or a leadless pacemaker; however, in the latter case, TR secondary to RV dysfunction associated with nonphysiological distribution of electric pulses or procedural complications can also occur.…”
Section: Transvenous Lead Extractionmentioning
confidence: 99%